Los ambientes de lectura y el disfrute literario en los niños de quinto año de la Unidad Educativa "Pedro Vicente Maldonado", Riobamba. Período 2021-2022. - Guacho Mullo, Diana Alexandra (2022)
In the Educational Unit "Pedro Vicente Maldonado" the impact that reading environments have on the literary enjoyment of students was evidenced, that by not offering an adequate space for this practice prevents them from appreciating this type of texts, not enjoying reading properly, not feeling motivation to read and limiting the development of a reading habit. For this, as a first point it was identified if the characteristics of the reading environment used meet the needs of the children, later the literary enjoyment of the students was related to the reading environment of the classroom and finally three strategies were proposed that help create an adequate reading environment, to encourage children to enjoy literary texts. This methodologically developed research was based on previous research and theories on reading environments and the literary enjoyment of children, had a mixed approach, its design is non-experimental, it was a bibliographic and field research, of descriptive level, the sample was of a non-probabilistic type applied to 33 students and 3 teachers of the fifth year. For the collection of information, two techniques and two instruments were used; a questionnaire structured through a survey with 10 closed questions for children and a closed interview of 6 items through an interview guide for teachers. The results obtained showed that the characteristics of the reading environment used in the classroom do not meet the needs of the students.